Collyriclosis in Red-backed shrikes Lanius collurio from Israel and Czech Republic - Osoba V. (Helminthologia, 2018)
One juvenile Red-backed shrike (Lanius collurio) with a cutaneous cyst of Collyriclum faba under its beak was observed in Israel on 13 October 2016. Another Red-backed shrike (adult female) with multiple cutaneous cysts around the vent was observed in Průhonice, Czech Republic on 19 June 2017. A third Red-backed shrike (adult male) with three cutaneous cysts around the vent was observed in Mariánské Radčice, Czech Republic on 16 July 2017. In the Israeli case, two adult trematodes C. faba were found in the cutaneous cyst. In the two Czech cases, C. faba was identified indirectly by analysing the cutaneous cyst morphology. C. faba had never been recorded previously in Israel.